Solving a Three-Body Continuum Coulomb Problem with Quasi-Sturmian Functions (Journal of Atomic and Molecular Sciences, 2013)
The scattering problem of three particles interacting via Coulomb potentials is studied using generalized parabolic coordinates. The scattering solutions areobtained by solving a driven equation. The ‘perturbation’ operator appearing in thedriven term is the non-orthogonal part of the kinetic energy operator. The approximated solution appearing in the driven term is the product of two two-body Coulombwave functions. As a test for our proposal, a simple two-dimensional model problemhas been solved numerically by using so called parabolic quasi-Sturmian basis representation. Convergence of the solution has been obtained as the basis set is enlarged.